Introducing Einsteinian Physics in High School and College - Arriassecq, Irene (2022)
This chapter reviews various proposals for teaching Einstein’s special and general theory of relativity in high school and college introductory courses and proposes two teaching-learning sequences for the last years of high school. They have been designed following a contextualized approach, within a theoretical framework that considers epistemological, psychological, and didactic aspects. It presents the teaching materials produced and someresults from implementation in real classroom settings.